Pendidikan Kesehatan Tentang Asi Eksklusif Pada Ibu Menyusui Di Desa Keleng Kec Kesugihan Kabupaten Cilacap - Septi Tri Aksari (JPS : Jurnal Pengabdian Serulingmas, 2021)
Exclusive breastfeeding is the feeding of breast milk only to the baby for 6 months without the addition of other foods and drinks such as formula milk, oranges, honey, tea water, except medicine, vitamins and minerals. Post partum mothers experience physical and psychological changes that can be affected by the COVID-19 pandemic. Mothers who cannot adapt to the postpartum critical period can experience psychological disorders that also affect breast milk production. Health education about exclusive breastfeeding in breastfeeding mothers in Keleng village aims to increase maternal knowledge about exclusive breastfeeding so that it is hoped that mothers will be more confident in breastfeeding, reduce anxiety and can apply it to their babies. Health education was attended by 20 post partum mothers in Keleng Village. The result of this community service is the provision of health education with a media booklet to increase mothers' confidence in giving exclusive breastfeeding to their babies, so that exclusive breastfeeding can be more adequate.